RACKET SPORTS AT THE ELEMENTARY SCHOOL´S PHYSICAL EDUCATION: PROPOSAL OF AN ALTERNATIVE METHODOLOGY FOR OVER 10 -YEAR OLD CHILDREN. (Fiep Bulletin - online, 2015)
The present work has the objective of proposing the systematization of pedagogical alternatives which aim at opportunizing the racket sports teaching-learning-training process at the Elementary School´s  Physical Education, applying, in practice, activiities and tasks with over 10-year-old children.The characteristics which behold the essence of racket sports have also been analysed, so that they can be initially tried out as a sport grouping, relating their similarities to the match´s tatics, understanding aspects and the general technical abilities. The study has been characterized as being literature review, and it  is based on framing the processes of the match´s incidental teaching to reach the racket sports learning through an intentional process.
Keywords: teaching-learning-training . Racket sports.Technical abilities.